SUMOylation in Neurological Diseases - Liu, F.-Y.; Liu, Y.-F.; Yang, Y.; Luo, Z.-W.; Xiang, J.-W.; Chen, Z.-G.; Qi, R.-L.; Yang, T.-H.; Xiao, Y.; Qing, W.-J.; W.-C. Li, D. (Current Molecular Medicine, 2016)
Since the discovery of SUMOs (small ubiquitin-like modifiers) over 20 years ago, sumoylation has recently emerged as an important posttranslational modification involved in almost all aspects of cellular physiology. In neurons, sumoylation dynamically modulates protein function and consequently plays an important role in neuronal maturation, synapse formation and plasticity. Thus, the dysfunction of sumoylation pathway is associated with many different neurological disorders. Hundreds of different proteins implicated in the pathogenesis of neurological disorders are SUMO-modified, indicating the importance of sumoylation involved in the neurological diseases. In this review, we summarize the growing findings on protein sumoylation in neuronal function and dysfunction. It is essential to have a thorough understanding on the mechanism how sumoylation contributes to neurological diseases in developing efficient therapy for these diseases.
Keywords: Sumoylation